Repositioning DPD Oversight in Aceh’s Licensing Qanun and Asymmetry - Mangunsong, Nurainun; Roiqoh, Surur (Jurnal Hukum IUS QUIA IUSTUM, 2025)
The enactment of Law No. 6 of 2023, which ratified the Job Creation Government Regulation in Lieu of Law (Perppu Cipta Kerja), has significantly reshaped Indonesia’s regulatory governance, particularly by streamlining business licensing through national standards. In Aceh, an autonomous region operating under asymmetric decentralization as established by Law No. 11 of 2006, these reforms have created friction with existing qanun, resulting in regulatory disharmony. This study analyzes the functional diffusion of the legislative oversight role of the Regional Representative Council (DPD RI) over licensing-related qanun in Aceh and evaluates its institutional effectiveness within the context of asymmetric decentralization. The research utilizes a juridical-empirical approach and qualitative methods. Data collection involved interviews and document analysis of qanun, DPD regulations, Constitutional Court decisions, and relevant statutory laws. Institutional and comparative analyses were conducted to examine the normative, structural, and functional dimensions of oversight, with references to countries that implement asymmetric decentralization. The findings indicate that DPD oversight in Aceh exemplifies functional diffusion driven by institutional requirements and limited regional coordination. Although symbolically important, its strategic impact is constrained by overlapping authorities, limited mandates, and insufficient stakeholder engagement. Comparative perspectives from Spain, India, and South Africa reveal alternative mechanisms for vertical legal harmonization through judicial or parliamentary means. Strengthening the DPD’s oversight function will require regulatory reform, increased institutional capacity, and enhanced collaboration among stakeholders to achieve substantive legislative oversight.